Stories for inclusive schools : developing young pupil's skills in assembly and in the classroom - Leicester, Mal.; Johnson, Gill, 1964- (London ; New York : RoutledgeFalmer, 2004)
These fictional stories have been written to illustrate and help teachers overcome the wide range of differences in children and the issues they face that can make them feel excluded. All activities are suitable for the classroom or assembly hall.
Book Cover -- Title -- Contents -- Introduction -- Jumping the Pipes -- Liveaboard About a Bit -- Tales from the Beach -- A Blurry World -- The Deal -- The Boq Factor -- One Step Ahead -- All of a Puzzle -- Ten Lengths of Chocolate -- A Secret -- Solo? -- Trainers.
Print version record.
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: Inclusive education; Storytelling; Values -- Study and teaching (Elementary) -- Activity programs; Mainstreaming in education; Mainstreaming, Education; Intégration scolaire; Art de conter; EDUCATION -- Inclusive Education; Mainstreaming in education; Inclusive education; Storytelling; Values -- Study and teaching (Elementary) -- Activity programs; Electronic books; Electronic books